Pengaruh Perasan Biji Pepaya (Carica papaya) terhadap Kerusakan Telur Argulus japonicus [The Influence of Papaya Seed (Carica papaya) Toward The Damage Eggs of Argulus japonicus] - Kismiyati Kismiyati; Sri Subekti; Ade Fitri Noor Inaya (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Argulus japonicus being parasite with blood sucking the host, do infestations by piercing the skin of the host through a maxillule and preoral stylet. The infestation causes ulceration and bleeding, thus giving access to secondary infection by bacteria, fungi, viruses, and causes death. The act of controlling against Argulus japonicus can be done by reduce in population which began in eggs stadium. Control over A.japonicus can use natural insecticide that is papaya seeds. Papaya seeds contain the active substance that are saponins, tannins, flavonoids, alkaloids which act as a natural insecticide. The research design was a completely randomized design with a treatment that were 0 ppt, 70 ppt, 80 ppt, 90 ppt, 100 ppt, and five replications. Data were analyzed by using analysis variance (ANAVA). The results showed that the juice of papaya seeds affect the egg damage of Argulus japonicus. Concentration of 100 ppt juice of papaya seeds can broken A. japonicus eggs with the largest percentage is 100%. Concentration of 90 ppt that percentage of eggs of A. japonicus were damaged by 83%, 74,25% of 80 ppt concentration, 59% of 70 ppt concentration, and 0% of control. Optimal concentration of papaya seeds which resulted in the amount of damage more than 50% of Argulus japonicus eggs is 80 ppt.